2019
DOI: 10.1038/s41467-019-08332-9
|View full text |Cite
|
Sign up to set email alerts
|

The cholesterol biosynthesis pathway regulates IL-10 expression in human Th1 cells

Abstract: The mechanisms controlling CD4+ T cell switching from an effector to an anti-inflammatory (IL-10+) phenotype play an important role in the persistence of chronic inflammatory diseases. Here, we identify the cholesterol biosynthesis pathway as a key regulator of this process. Pathway analysis of cultured cytokine-producing human T cells reveals a significant association between IL-10 and cholesterol metabolism gene expression. Inhibition of the cholesterol biosynthesis pathway with atorvastatin or 25-hydroxycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 65 publications
5
80
0
Order By: Relevance
“…Of note, a pathway analysis revealed that the top five canonical pathways upregulated in NCOR1deficient naïve CD4 + T cells displayed an overrepresentation of cholesterol biosynthesis pathways (Supplementary Figure 2B), further supporting the conclusion that NCOR1 regulates cholesterol metabolism in naïve CD4 + T cells. Upon CD4 + T cell activation cholesterol biosynthesis is increased and its metabolites are crucial for Th effector differentiation and function (47)(48)(49). Cholesterol homeostasis gene sets were not enriched in NCOR1-deficient Th1 or Th17 cells, suggesting a specific role for NCOR1 in naïve CD4 + T cells in setting up transcriptional programs required for cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…Of note, a pathway analysis revealed that the top five canonical pathways upregulated in NCOR1deficient naïve CD4 + T cells displayed an overrepresentation of cholesterol biosynthesis pathways (Supplementary Figure 2B), further supporting the conclusion that NCOR1 regulates cholesterol metabolism in naïve CD4 + T cells. Upon CD4 + T cell activation cholesterol biosynthesis is increased and its metabolites are crucial for Th effector differentiation and function (47)(48)(49). Cholesterol homeostasis gene sets were not enriched in NCOR1-deficient Th1 or Th17 cells, suggesting a specific role for NCOR1 in naïve CD4 + T cells in setting up transcriptional programs required for cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…While de novo FAS has been shown to play an important role in effector CD4 + T cell functions, cholesterol metabolism is involved in the regulation of the anti-inflammatory response in human CD4 + T cells (Perucha et al, 2019). Inhibition of the cholesterol biosynthesis pathway with atorvastatin or 25-hydroxycholesterol during switching from IFNγ + to IL-10 + showed a specific block in immune resolution, defined as a significant decrease in c-Maf/IL-10 expression (Perucha et al, 2019).…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…IL-10 is an anti-inflammatory and pro-resolving factor that can work to inhibit pro-inflammatory cytokines [22] . Increased IL-4 is associated with allergic airway response; [23] and both IL-4 and IL-10 alter macrophage lipid metabolism [24] . However, in a separate study from our group, IL-4 and IL-10 were not affected by e-cig use in never-smokers, although the study was of brief duration [25] .…”
Section: Discussionmentioning
confidence: 99%